Elementary School Teachers Perceptions of Digital Learning Media Innovations in Implementing the Merdeka Curriculum - Heny Amalia Choirunnisa; Titi Anjarini; Nur Ngazizah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Learning media innovation relates to the process of creating learning media with novelty to provide a new revolution in teaching and learning activities. This process depends on the perception of teachers at the primary school level, which can be defined as a person’s understanding or thought of an object that will be interpreted through the five senses. The purpose of this research is to find out how elementary school teachers perceive learning media innovations with digital games in implementing of independent curriculum. This research is qualitative in nature and uses descriptive methods with the research subject being teachers in one of the private elementary schools located in Bayan District, Purworejo. The interview technique was used to collect data from teachers to find out their perceptions specifically. The data obtained will be analyzed using the Miles and Huberman technique. The results showed that teachers agreed with the existence of digital games as one possible way to explore learning media innovations to support the implementation of the independent curriculum. Teachers responses to digital games are thought to be able to follow the needs of children who like to play and can minimize the use of digital games that do not contain learning elements so that they are very practical to be integrated in teaching and learning activities. It can be concluded that the perception of teachers who accept the existence of digital games as a learning media innovation is the first step to be implemented in the teaching and learning process both online, hybrida, and face-to-face so that it can keep up the times.